2013
DOI: 10.4172/2167-1095.1000147
|View full text |Cite
|
Sign up to set email alerts
|

Silent Crisis: Epidemic Hypertension in Rural West Africa

Abstract: The Barekese sub-district of Ghana is a rural community near Kumasi, Ghana's second largest city, where investigators have previously identified a high burden of hypertension along with poor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In addition, factors like changes in diet, lifestyle, and the rising prevalence of obesity may contribute to finding a higher prevalence of hypertension in this study ( 12 ). Although the finding is in line with a study conducted in a rural community of Barekese in Ghana, where 438 adults aged ≥ 35 had a prevalence rate of 50.9% ( 26 ). However, a systematic review and a meta-analysis on the prevalence of adult hypertension in Ghana conducted by Bosu and Bosu ( 27 ) found a 27.0% pooled prevalence of hypertension which is relatively lower than the findings of this study but similar to that of Nigeria (28.9%) ( 28 ), Cameroon (30.9%) ( 29 ), Sub-Saharan Africa (30.0%) ( 30 ), Ethiopia (19.6%) ( 31 ), and of 44 developing countries (17.5%) ( 32 ).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, factors like changes in diet, lifestyle, and the rising prevalence of obesity may contribute to finding a higher prevalence of hypertension in this study ( 12 ). Although the finding is in line with a study conducted in a rural community of Barekese in Ghana, where 438 adults aged ≥ 35 had a prevalence rate of 50.9% ( 26 ). However, a systematic review and a meta-analysis on the prevalence of adult hypertension in Ghana conducted by Bosu and Bosu ( 27 ) found a 27.0% pooled prevalence of hypertension which is relatively lower than the findings of this study but similar to that of Nigeria (28.9%) ( 28 ), Cameroon (30.9%) ( 29 ), Sub-Saharan Africa (30.0%) ( 30 ), Ethiopia (19.6%) ( 31 ), and of 44 developing countries (17.5%) ( 32 ).…”
Section: Discussionsupporting
confidence: 90%
“…The first of these studies in 425 adults aged ≥35 years reported a prevalence of hypertension of 44.7% [ 130 ]. Concerned about this high prevalence in the rural community, the investigators repeated the study the following year in 438 adults aged ≥35 years and confirmed their earlier study with an even higher prevalence of 50.9% [ 131 ]. Then, in 2012, the investigators conducted another study in the same community, this time sampling 845 adults aged ≥18 years and found a prevalence of isolated systolic hypertension of 30.6%.…”
Section: Discussionmentioning
confidence: 56%
“…Inspired by this observation, we described an ‘epidemic of hypertension’ in our systematic review of 2010 [ 12 ]. Since then, a rural epidemic of hypertension [ 131 ] and a national epidemic of obesity in Ghana have been described [ 18 ]. Of particular concern is our finding that the urban-rural gap in the prevalence of hypertension has become blurred and that the high prevalence has persistent over four decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The burden is not peculiar to urban areas as studies in rural areas in sub-Saharan Africa have also revealed a high rate. (21)(22)(23) Reports have shown that urban populations consistently have higher prevalence of hypertension than their rural counterparts in almost all studies that covered both area (15). This observation has been suggested to be linked with increased levels of obesity, salt and fat intake from increased consumption of processed foods, and engaging in jobs with minimal physical activity and smoking.…”
Section: P R E V a L E N C E O F H Y P E R T E N S I O Nmentioning
confidence: 99%